Mobile application for registration and diagnosis of respiratory diseases: a review of the scientific literature between 2010 and 2020 - Flores Rodriguez, Jazmin Rosa Maria (2021)
ABSTRACT In early 2020, an unknown aetiological pneumonia named by the World Health Organization (WHO) as COVID-19, is causing the death of millions of people around the world. At present, there is no treatment or vaccine against the disease, so the need to find various strategies to combat it is urgent. This document used a systematic review of the literature (SLR) as a method, where the objective is to identify the benefits of mobile applications that allow the registration and diagnosis of respiratory diseases. For the research, a literature review was conducted in databases such as Scielo, IEEE Xplore, Proquest, Ebsco, Scopus, Google academic and WoS from which 60 scientific articles were obtained between the periods 2010-2020. Of the 60 articles found, they were synthesized in 12 groups in relation to the topic, of which 11 articles were related to medical chatbot, which showed positive effects regarding the influence of a mobile application for the diagnosis of diseases.